Oxidative and nitrosative stress in patients with meningitis - Namiduru, Emine Siber; Namiduru, Mustafa; Karaoğlan, İlkay and Koçak, Kübra (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Meningitis is an acute inflammation of the protective membranes covering the brain and spinal cord, known as the meninges. In this study, oxidative and nitrosative stress were evaluated in cerebrospinal fluid (CSF) and blood samples that were taken from patients with meningitis. Our goal was to identify a fast and a reliable biomarker using these parameters in order to the early diagnose of bacterial meningitis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. In this study, 37 bacterial meningitis, 30 tuberculous meningitis and 30 viral meningitis cases were included. Serum/CSF total oxidant status (TOS) and total antioxidant status (TAS) were measured by the Erel method. Nitrotyrosine concentrations were quantified by using ELISA in both serum and CSF. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Serum nitrotyrosine, CSF TAS and TOS levels were not significantly different in three groups (p>0.05). CSF nitrotyrosine levels were significantly higher in bacterial meningitis than tuberculous meningitis group (p<0.05). Viral meningitis patients had higher serum TOS and TAS concentrations than tuberculous meningitis group (p<0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. As a result, we can say that the oxidative and nitrosative stress markers studied are not a rapid and reliable biomarker in bacterial meningitis’s diagnosis.